(untitled) (Research, Society and Development, 2022)
This study aimed to describe how the middle-range theory for nursing in cardiovascular rehabilitation, based on the use of the nursing process, contributed to the cardiovascular rehabilitation process in patients with heart failure. A quasi-experimental, non-randomized study was performed, using a pre- and post-intervention approach. The sample consisted of 16 patients hospitalized in a referral unit for the treatment of heart failure. A total of 14 priority nursing diagnoses were identified for the participants. The most incident nursing diagnoses were anxiety, fear, activity intolerance and fatigue. It can be concluded that assistance in the light of the middle-range theory for nursing in cardiovascular rehabilitation favors an adequate rehabilitation process for patients with heart failure, as there was a reduction in the manifestation of priority diagnoses in patients with heart failure, thus allowing more comfort and quality of life, which are essential elements for the cardiovascular rehabilitation process.